IBS survey 2010: Drivers, barriers and critical success factors in adopting industrialised building system (IBS) construction by G7 contractors in Malaysia - Mohamad Kamar, Kamarul Anuar; Azman, Mohamed Nor Azhari; Mohd Nawi, Mohd Nasrun (School of Engineering, Taylor’s University, 2014)
The industrialised building system (IBS) survey has become an essential tool for ensuring the IBS Roadmap (2003 to 2010) meets its goals and target.As part of the process review survey, it also records the trend ac hievement of Malaysia in the usage of IBS in the building construction industry.The first and second IBS surveys were published in 2003 and 2005, respectively.Afterward, the IBS Roadmap’s mid-term review was conducted.The third and the most recent IBS surveys were conducted in 2008 and 2010, respectively.This paper aims to highlight a part of the IBS survey report in 2010, which has been conducted to measure the drivers, barriers and the critical success factors of G7 con tractors in adopting IBS construction.G7 is a Construction Industry Development Board contractor grade that can apply tender without limit.The importance of this paper is that it guides the policy and implementation strategy of IBS by G7 contractors.The survey shows that the acceptance, adoption, and deployment of IBS in the Malaysian construction industry are still low and do not address the persisting problems, such as productivity, dependency on foreign workers and high level of construction wastage.